2014
DOI: 10.1016/j.tca.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Thermal investigations of Ti and Ag-doped bioactive glasses

Abstract: To cite this version:Eric Wers, Hassane Oudadesse, Bertrand Lefeuvre, Bruno Bureau, Odile Merdrignac-Conanec. Thermal investigations of Ti and Ag-doped bioactive glasses. Thermochimica Acta, Elsevier, 2014, 580, pp.79-84 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…However, it can be seen that the cell viability decreases with copper oxide content in the samples. The pH behaviour is a relevant variable as the cells are highly sensitive to changes in the physiological media (pH = 7.4; Bejarano, Caviedes, & Palza, ; Wers, Oudadesse, Lefeuvre, Bureau, & Merdrignac‐Conanec, ). Evaluating the pH changes after 24 hr by immersing the composites in SBF solution, it was found that the solution pH increased from 7.4 to 7.5 and 7.6 for Alg‐Pll‐0.5CuBG and Alg‐Pll‐1.5CuBG, respectively.…”
Section: Resultssupporting
confidence: 89%
“…However, it can be seen that the cell viability decreases with copper oxide content in the samples. The pH behaviour is a relevant variable as the cells are highly sensitive to changes in the physiological media (pH = 7.4; Bejarano, Caviedes, & Palza, ; Wers, Oudadesse, Lefeuvre, Bureau, & Merdrignac‐Conanec, ). Evaluating the pH changes after 24 hr by immersing the composites in SBF solution, it was found that the solution pH increased from 7.4 to 7.5 and 7.6 for Alg‐Pll‐0.5CuBG and Alg‐Pll‐1.5CuBG, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Zinc, titanium, copper, silver, magnesium, and strontium ions can be introduced in the amorphous matrix of a bioactive glass [88,[122][123][124][125][126]. They are used to improve different characteristics such as the mechanical properties, chemical reactivity, and biological properties.…”
Section: Zn-and Ti-doped Bioactive Glassesmentioning
confidence: 99%
“…The effect of Ti on the thermal behavior of 46S6 is presented in Figure 16 [123]. When the Ti content increases from 0.1 wt% to 10 wt%, the crystallization temperature increases from 611°C to 700°C, whereas the effect on the glass transition temperatures is less pronounced (increasing from 548°C to 576°C).…”
Section: Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Doping bioactive glasses with functional ions is important to modify their properties and enhance their interaction with the human body. Nevertheless, in most cases the doping ions were added separately, and their investigated effects were not compared to a parent glass (Bejarano, Detsch, Boccaccini, & Palza, 2017;Tylkowski & Brauer, 2013;Wers, Oudadesse, Lefeuvre, Bureau, & Merdrignac-Conanec, 2014). There have been a few systematic studies of combined doping with multiple elements, such as binary Sr 2+ -Li + dopants (Khan et al, 2016), but no such binary studies have been made on solgel derived bioglass.…”
mentioning
confidence: 99%